2014
DOI: 10.1016/j.rbmo.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Severe haematoperitoneum caused by ovarian bleeding after transvaginal oocyte retrieval: A retrospective analysis and systematic literature review

Abstract: A case series of haematoperitoneum caused by ovarian bleeding after transvaginal oocyte retrieval (TVOR) is presented and all published cases summarized. In a retrospective case series, four patients with ovarian bleeding after TVOR were included. In addition, a pooled analysis of all published cases (n = 32) who underwent surgical intervention for severe haematoperitoneum caused by ovarian bleeding after TVOR was carried out. Main outcome measures were incidence, risk factors, course and intraoperative findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 36 publications
2
26
0
2
Order By: Relevance
“…The incidence of severe hemoperitoneum was 0.08% in 2007, decreasing 0.29-fold by 2015 in Japan [ 8 ]. Severe hemoperitoneum symptoms usually appear within 24 hours after oocyte retrieval procedures [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of severe hemoperitoneum was 0.08% in 2007, decreasing 0.29-fold by 2015 in Japan [ 8 ]. Severe hemoperitoneum symptoms usually appear within 24 hours after oocyte retrieval procedures [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presented case indicated a group of patients who are more prone to complications in different circumstances of reproductive age. Key words: hemoperitoneum; in vitro fertilization; ovarian cyst; preterm labor renja uključuje kirurški zahvat u općoj anesteziji radi postizanja hemostaze i vitalnog zbrinjavanja pacijentice, što je ozbiljna posljedica uobičajeno jednostavnog liječenja neplodnosti, koje se obavlja ambulantno 5 . U ovome članku bit će prikazan slučaj pacijentice s ponavljajućom rupturom jajnika -prvi put nakon aspiracije jajnih stanica u stimuliranom IVF ciklusu, a zatim nakon dugog vremenskog razdoblja drugi put, nakon prijenosa zametka u prirodnom ciklusu.…”
Section: Discussionunclassified
“…10 Severe hemoperitoneum, 10,11 massive hematuria, 12 rupture of ovary causing hemorrhagic shock 13 and uterovaginal fistula formation 14 have been reported as OPU-related complications. Aragona et al reported the incidence of severe complications and intraperitoneal bleeding, in their 7,098 IVF cycle series, to be 0.08% and 0.06%, respectively.…”
Section: Discussionmentioning
confidence: 99%